Effects of supplemental viscous damping on inelastic seismic response of asymmetric systems. - Goel, Rakesh K. (Earthquake engineering & structural dynamics.)
This paper investigates the effects of supplemental viscous damping on the seismic response of one storey, asymmetric plan systems responding in the inelastic range of behaviour. It was found that addition of the supplemental damping reduces not only deformation demand but also ductility and hysteretic energy dissipation demands on lateral load resisting elements during earthquake loading. However, the level of reduction strongly depends on the plan wise distribution of supplemental damping. Nearly optimal reduction in demands on the outermost flexible side element, an element generally considered to be the most critical element, was realized when damping was distributed unevenly in the system plan such that the damping eccentricity was equal in magnitude but opposite in algebraic sign to the structural eccentricity of the system. These results are similar to those noted previously for linear elastic systems, indicating that supplemental damping is also effective for systems expected to respond in the inelastic range.